Revalorisation of brewer’s spent grain for biotechnological production of hydrogen with Escherichia coli - Cabrera, Gema; Jáimez, José Manuel; Sánchez-Oneto, Jezabel; Bolivar, Jorge; Valle, Antonio (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Agro-industrial wastes are generated in huge amounts triggering damages to the environment and human health. Therefore, there is an urgent necessity for its revalorisation into high-value compounds, including biofuels. One such wastes is the brewer's spent grain (BSG), a by-product of the beer industry, which is produced in vast quantities worldwide. The rich-fibre and protein content of BSG makes this waste a valuable resource for biotechnological applications, although the main challenge of this approach is to make the carbohydrates and proteins available for bacterial metabolisation into high-value products. This work aims to optimise a thermal-hydrolysis process to revalorise BSG by bacterial conversion into hydrogen (H2), as a clean energy that can replace fossil fuels. Methods A 2k full factorial design method was employed hydrolysation of BSG and showed that temperature and acid concentration are significant factors that affect the extraction of reducing sugars (RS) and proteins. Subsequently, steepest ascent and central composite design (CCD) statistical methods were applied to determine the optimal conditions for hydrolysis. Results The optimised hydrolysis condition were 0.047 M H2SO4, 150°C, 30 min and 15% BSG, leading to the theoretical concentrations of 54.8 g RS/L and 20 g/L proteins. However, 5'-hydroxymethylfurfural (HMF) was generated in thermal-hydrolysis conditions at higher temperatures exceeding 132°C. Therefore, a screening of HBSGs fermentation using Escherichia coli was conducted in order to identify the most suitable conditions for maximizing H2, as well as the production of volatile fatty acids (succinate and acetate) and ethanol. Among the tested conditions, HBSG A17 (117°C, 20 min, and 0.1 M H2SO4) yielded the highest H2 production of 48 mmol/L in this work. Conclusion This study provides valuable insights into the optimisation of BSG pre-treatment for biotechnological applications, which may help in the selection of the most appropriate hydrolysis conditions based on the desired end product.